Obraz edukacji wczesnoszkolnej w wypowiedziach nauczycieli edukacji przedmiotowej - Józefa Bałachowicz; Monika Kupiec (Problemy Wczesnej Edukacji)
A look at the adaptation of students crossing the second educational threshold in the perspective of constructivism makes it clear that it is important to reach ways of thinking about early childhood education of 4th grade teachers. The early-school education model adopted by them translates to a large extent into the perception and evaluation of the resources of the 4th grade, which, in turn, sets the direction of the teaching communication activity in the school class, creating an environment for the student’s adaptation process at the beginning of learning in the 4th grade. The presented research adopts a phenomenographic perspective of collecting and analyzing data from semi-structured interviews with Polish language teachers from one environment. The results reveal how teachers describe and value early childhood education as a source of 4th grade resources. These ways of thinking about early school education, focusing on its determinants, have been interpreted as discursive knowledge. Based on the theory of Bernstein’s socio-pedagogical codes, an attempt was made to describe the mechanism of consolidating this perception of early childhood education. The dominant teaching discourse reveals the depreciation of the child’s previous experience related to the conditions of early school education, e.g. one teacher, active learning and teaching methods, descriptive assessment; and thus strengthens the obviousness of the hardships and failures of the Fourth graders that have always been experienced.